รูปแบบการดำเนินงานโครงการที่พักนักท่องเที่ยวที่มีแนวคิดวิสาหกิจเพื่อสังคม : กรณีศึกษา ชุมพรคาบาน่า รีสอร์ต และโรงแรมสวนสามพราน - ชญตา ลีวงศ์เจริญ (จุฬาลงกรณ์มหาวิทยาลัย, 2022)
Currently, an increasing number of businesses are implementing the Social Enterprise (SE) concept, which aims to benefit both society and the environment. However, implementation of this concept in the tourist accommodation sector remains limited, despite the potential for businesses applying this concept to have a significant positive impact on society and the environment. This article focuses on the implementation of the SE concept in two case studies: the Chumphon Cabana Resort and the Suan Sampran Hotel. Data collection was conducted through literature reviews, field surveys, and interviews with key informants, including each business owner and 5 stakeholders per case study, as well as 20 tourists per case study. The collected data were analyzed using a comparative analysis method, presenting the findings in terms of SE components and their relationships. Lessons learned are also derived from cases.The study found that, firstly, both cases applied the idea of SE as a core concept for their business, despite having different starting points. The Chumphon Cabana Resort, for instance, utilized this idea to tackle its debt issues, while the Suan Sampran Hotel used it to create sales opportunities. Secondly, the SE concept implemented by both tourist accommodations involved two key components. 1) The stakeholders involved in the development of the projects can be divided into three main groups: the core business group, including network businesses; the beneficiaries; and the supporters from various sectors. 2) There were five main activities, which were similar in both cases: (1) providing knowledge management support to stakeholders, i.e., farmers and hotel staff, (2) purchasing agricultural products from farmers at fair prices, (3) adding value to agricultural products through business production, (4) providing markets and distributing agricultural products, and (5) supporting sustainable tourism development. Lastly, the impact in four dimensions was as follows: (1) economic impact, leading to the creation of added economic value, job opportunities, and income distribution; (2) social impact, enhancing the community s quality of life and creating sustainable self-reliance; (3) environmental impact, promoting activities that reduce environmental harm; and (4) business impact, by generating added value and creating unique selling points.The study reflects that the operations of SE tourism accommodation projects in both cases have had a significant impact on stakeholders and society. The lessons learned as key success factors are that intention and understanding of development are required for entrepreneurs strategically planning for change. Furthermore, the stakeholders’ participation must be included in the SE process. This research can serve as a guide for tourism entrepreneurs interested in applying the concept of social entrepreneurship in their development projects.